2012
DOI: 10.1093/jat/bks067
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lowering Confirmatory Test Cutoff Value in Pre-Enlistment Urine Cannabinoids Screening: About Five Years' Experience in the French Gendarmerie

Abstract: The guidelines for screening of urinary cannabinoids require that all specimens testing positive should be confirmed by gas chromatography-mass spectrometry at a confirmatory test cutoff value of 15 ng/mL of 11-nor-9-carboxy-Δ9-tetrahydrocannabinol (THCCOOH). To assess the impact of lowering the confirmatory test cutoff value on the diagnostic sensitivity and efficiency of a cannabinoid testing program, the results of 986 confirmation analyses of positive screening tests, conducted in the framework of medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Monitoring cannabis cessation or consumption is generally based on the determination of cannabinoids in urine, using automatized immunoassay methods with cut‐offs values of 20 or 50 ng/mL to discriminate between positive and negative samples. Fifty ng/mL is a widely used cut‐off with strong sensitivity and specificity, but it has been suggested that a screening test threshold of 20 ng/mL could improve sensitivity while preserving the specificity . Some covariates affect the urinary concentration of cannabinoids, including consumption frequency, intensity and period, body fat, body mass index (BMI), and urine dilution according to solute intake and hydration status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring cannabis cessation or consumption is generally based on the determination of cannabinoids in urine, using automatized immunoassay methods with cut‐offs values of 20 or 50 ng/mL to discriminate between positive and negative samples. Fifty ng/mL is a widely used cut‐off with strong sensitivity and specificity, but it has been suggested that a screening test threshold of 20 ng/mL could improve sensitivity while preserving the specificity . Some covariates affect the urinary concentration of cannabinoids, including consumption frequency, intensity and period, body fat, body mass index (BMI), and urine dilution according to solute intake and hydration status.…”
Section: Introductionmentioning
confidence: 99%
“…Fifty ng/mL is a widely used cut-off with strong sensitivity and specificity, but it has been suggested that a screening test threshold of 20 ng/mL could improve sensitivity while preserving the specificity. 8 Some covariates affect the urinary concentration of cannabinoids, including consumption frequency, intensity and period, body fat, body mass index (BMI), and urine dilution according to solute intake and hydration status. However, sensitivity and specificity of the analytical method used could also affect the detection window of these compounds.…”
mentioning
confidence: 99%